The Effects of Resveratrol on Silica-Induced Lung Oxidative Stress and Inflammation in Rat - Maryam Esfahani; Amir Hossein Rahbar; Sara Soleimani Asl; Saed Bashirian; Effat Sadat Mir Moeini; Fereshteh Mehri (Safety and Health at Work, 2023)
Background: Chronic exposure to silica is related with the provocation of an inflammatory response and oxidative stress mechanism. Vitamin D has multiple benefits in biological activities particularly respiratory system disease. Method: In this research, 20 male Wistar rats were randomly allocated into four groups (5 rats /group) as follow: Group1 received saline as (negative control) group. The group 2 received a single IT instillation of silica (positive control) group; the group 3 was co-administrated with single IT silica and Vitamin D (20 mg/kg/day) daily for a period of 90 days. The rats of group 4 received Vitamin D daily for a period of 90 days. Results: Silica significantly increased serum and lung total Oxidant Status (TOS). Meanwhile, silica reduced serum and lung total antioxidant capacity (TAC), GSH and tumor necrosis factor-α (TNF-a). Vitamin D treatment meaningfully reversed oxidative stress, antioxidants status and inflammatory response. Also, Vitamin D improved histopathological changes caused by silica. Conclusion: These findings indicate that Vitamin D exerts protective effects against silica-induced lung injury. It seems that Vitamin D has potential use as a therapeutic object for silica induced lung injure.